Digital food and beverage marketing appealing to children and adolescents: An emerging challenge in Mexico - Nieto, Claudia; Espinosa, Fiorella; Valero-Morales, Isabel; Boyland, Emma; Potvin Kent, Monique; Tatlow-Golden, Mimi; Ortiz-Panozo, Eduardo; Barquera, Simon (Université d'Ottawa | University of Ottawa, 2023)
Background: Digital food marketing is increasing and has an impact on children's behaviour. Limited research has been performed in Latin America. Objectives: To determine the extent and nature of Mexican children's and adolescents' exposure to digital food and beverage marketing during recreational internet use. Methods: A crowdsourcing strategy was used to recruit 347 participants during the COVID-19 lockdown. Participants completed a survey and recorded 45 minutes of their device's screen time using screen-capture software. Food marketing was identified and nutrition information for each marketed product was collected. Healthfulness of products was determined using the Pan-American Health Organization and the Mexican Nutrient Profile Model (NPM). A content analysis was undertaken to assess marketing techniques. Results: Overall, 69.5% of children and adolescents were exposed to digital food marketing. Most frequently marketed foods were ready-made foods. Children and adolescents would typically see a median of 2.7 food marketing exposures per hour, 8 daily exposures during a weekday and 6.7 during a weekend day. We estimated 47.3 food marketing exposures per week (2461 per year). The most used marketing technique was brand characters. Marketing was appealing to children and adolescents yet most of the products were not permitted for marketing to children according to the NPMs (>90%). Conclusions: Mexican children and adolescents were exposed to unhealthy digital food marketing. The Government should enforce evidence-based mandatory regulations on digital media.
Keywords: adolescents; children; digital food marketing; food marketing; internet